Validation of farmer to farmer extension model for dissemination of quality seeds of pulse crops: experiences from Bundelkhand Region of Uttar Pradesh - Uma Sah, Narendra Kumar, Hem Saxena, S.K. Dubey, M.A. Iquebal, Shripad Bhat and S.K. Singh, (Indian Journal of Extension Education, 2018)
The study was conducted during 2010-14 at Indian Institute of Pulses Research (IIPR), Kanpur among 143farmers from Jalaun district of Bundelkhand region of India. The key farmers were provided quality seeds ofimproved pulse varieties and they were asked to diffuse the seeds in a pre designed structured manner to otherfarmers in their social networks after the harvest. Logit model was used to analyze the factors associated withfarmers’ decision to follow the structured diffusion of improved pulse varieties. Study revealed that majorityof the farmers preferred 1:1 ratio for structured diffusion. The structured diffusion varied significantly, withrespect to years and pulse crops. Variables like educational level, social participation, yield advantage accrued,attitude level and training exposure significantly determined the decision of farmer to follow the structureddiffusion of quality seeds of pulse crops.